Neogene to Quaternary uplift history along the passive margin of the northeastern Arabian Peninsula, eastern Al Hajar Mountains, Oman. Issue 2 (20th August 2018) - Moraetis, Daniel; Mattern, Frank; Scharf, Andreas; Frijia, Gianluca; Kusky, Timothy M.; Yuan, Ye; El-Hussain, Issa
Abstract: This work explores the uplift history of the best exposed marine terraces in the northeastern Arabian Peninsula (eastern Al Hajar Mountains). A multidisciplinary approach was employed, including a topographic survey, 14 C dating, thin section studies, and scanning electron microscopy analyses. Six distinctive marine terraces with widths ranging from tenth of meters to kilometers and elevations from 5 to ~400 m were studied. These terraces record an along-strike heterogeneous uplift history, while they show temporally variable uplift rates ranging between 0.9 to 6.7 mm/yr, which correlates well with other published uplift rates of marine terraces of the eastern Arabian Peninsula. We attribute the variable uplift along strike of the terraces, to a combination of uplift mechanisms: (1) during early to mid-Miocene along deep-rooted reverse faults that bound large crustal-scale blocks, (2) Pliocene or post-Pliocene uplift on the outer wall of the forebulge of the lower Arabian Plate as it bends to enter the Zagros-Makran subduction zone, and (3) a possible slowdown of subduction for the past ~40 ka.